Molecular dynamics study of aluminum bronze nanograin surfacing - Nikonov, Anton Yu; Lychagin, Dmitry V.; Bibko, Artem A.; Novitskaya, Olga S. (Russian physics journal)
The amount of heat input during surfacing affects the structure and properties of a product. Features of the crystallizing structure depend on the structure of the already deposited layers. The process of structural changes during the interaction of a melt drop with the basis of three grains has been traced by modeling using the molecular dynamics method. The grain parameters in the model are set from the experimental characteristics of the sample obtained by electron-beam surfacing of aluminum bronze. Increasing the temperature of the melt drop improves its spreading and increases the melting depth. The grain growth during crystallization inherits the grain orientation of the basis. During crystallization, stacking faults and twins are formed, oriented similarly to defects in the basis. The grain boundaries change orientation in the direction of the maximum temperature gradient.